2007
DOI: 10.1128/jb.01427-06
|View full text |Cite
|
Sign up to set email alerts
|

CapA, an Autotransporter Protein ofCampylobacter jejuni, Mediates Association with Human Epithelial Cells and Colonization of the Chicken Gut

Abstract: Two putative autotransporter proteins, CapA and CapB, were identified in silico from the genome sequence of Campylobacter jejuni NCTC11168. The genes encoding each protein contain homopolymeric tracts, suggestive of phase variation mediated by a slipped-strand mispairing mechanism; in each case the gene sequence contained frameshifts at these positions. The C-terminal two-thirds of the two genes, as well as a portion of the predicted signal peptides, were identical; the remaining N-terminal portions were gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(106 citation statements)
references
References 66 publications
1
105
0
Order By: Relevance
“…The identified genes encode membrane transporters (Cj0035c, Cj0366c, Cj0561c, and Cj1619), proteins involved in C 4 -dicarboxylate transport or utilization and metabolism (Cj0087, Cj0088, Cj0671, Cj0437, Cj0264c, and Cj0119), enzymes for capsular polysaccharide biosynthesis (Cj1424c, Cj1426c, Cj1427c, Cj1428c, Cj1429c, Cj1430c, and Cj1432c), periplasmic proteins or lipoproteins (Cj0089, Cj0091, Cj0092, Cj0628/Cj0629, and Cj0854c), a putative transcriptional factor (Cj1563c, a MerR homolog), a putative iron-binding protein (Cj0241c), a putative purine nucleoside triphosphate pyrophosphatase (Cj1374c), and hypothetical proteins (Cj0040 and Cj0583). Cj0628 and Cj0629 were originally annotated as two separate genes (32), but recent work showed that these two genes form a single ORF encoding an autotransporter protein (2). Differential expression of the identified genes in 11168W7 and 11168W7⌬cmeR.…”
Section: Identification Of the Native Promoter Of Cmermentioning
confidence: 99%
“…The identified genes encode membrane transporters (Cj0035c, Cj0366c, Cj0561c, and Cj1619), proteins involved in C 4 -dicarboxylate transport or utilization and metabolism (Cj0087, Cj0088, Cj0671, Cj0437, Cj0264c, and Cj0119), enzymes for capsular polysaccharide biosynthesis (Cj1424c, Cj1426c, Cj1427c, Cj1428c, Cj1429c, Cj1430c, and Cj1432c), periplasmic proteins or lipoproteins (Cj0089, Cj0091, Cj0092, Cj0628/Cj0629, and Cj0854c), a putative transcriptional factor (Cj1563c, a MerR homolog), a putative iron-binding protein (Cj0241c), a putative purine nucleoside triphosphate pyrophosphatase (Cj1374c), and hypothetical proteins (Cj0040 and Cj0583). Cj0628 and Cj0629 were originally annotated as two separate genes (32), but recent work showed that these two genes form a single ORF encoding an autotransporter protein (2). Differential expression of the identified genes in 11168W7 and 11168W7⌬cmeR.…”
Section: Identification Of the Native Promoter Of Cmermentioning
confidence: 99%
“…Adherence involves different types of lectin-like molecules attaching to their corresponding glycosylated receptors on the epithelial cells (Guerry et al, 2002). Major outermembrane proteins such as the putative rod-shapedetermining protein MreB, the putative periplasmic protein MreC and C. jejuni lipoprotein JlpA play important roles in bacterial adhesion (Ashgar et al, 2007;del Rocio Leon-Kempis et al, 2006;Jin et al, 2003;Kakuda & DiRita, 2006;Karlyshev et al, 2000;Konkel et al, 1997;Linton et al, 2000;Mamelli et al, 2006;McSweegan & Walker, 1986;Monteville & Konkel, 2002;Moser et al, 1997;Pei & Blaser, 1993). The genes encoding these three proteins were upregulated in response to MUC2.…”
Section: Muc2 Concn (Mg MLmentioning
confidence: 99%
“…CapA mutant showed decreased adherence to human Caco-2 cells and also low colonisation efficiency in chicks [25]. In another study, mutation of capA also showed decreased adherence to chicken epithelial cells in vitro, although it did not result in a reduced ability of mutants to colonise chicks (47%) [17].…”
Section: Unconfirmed and Putative Adhesion-related Proteinsmentioning
confidence: 99%
“…According to Sanger Institute annotation capB gene was assigned two pairs of ORFs, in the same way as capA. In contrast to CapA, playing a role in adhesion to cultured cells, no expression of CapB was detected [25]. Due to high level of amino acid sequence similarity between the two proteins, CapB might also be considered a putative adhesin.…”
Section: Contradictory Datamentioning
confidence: 99%
See 1 more Smart Citation